Сравнительно-морфологическая характеристика предкуколок рода Hoplitis (Hymenoptera, Megachilidae) - Ромасенко, Л.П. (Вестник зоологии, 1993)
A review of all known prepupae of the holarctic genus Hoplitis Klug. A complex of diagnostic characters at generic and specific rank is outlined. An original key to 9 species on prepupae characters is given.